Quantifying the Size and Duration of a Microburst‐Producing Chorus Region on 5 December 2017 - S. S. Elliott; A. W. Breneman; C. Colpitts; J. M. Pettit; C. A. Cattell; A. J. Halford; M. Shumko; J. Sample; A. T. Johnson; Y. Miyoshi; Y. Kasahara; C. M. Cully; et al. (Geophysical Research Letters)
Abstract Microbursts are impulsive (<1 s) injections of electrons into the atmosphere, thought to be caused by nonlinear scattering by chorus waves. Although attempts have been made to quantify their contribution to outer belt electron loss, the uncertainty in the overall size and duration of the microburst region is typically large, so that their contribution to outer belt loss is uncertain. We combine datasets that measure chorus waves (Van Allen Probes [RBSP], Arase, ground‐based VLF stations) and microburst (>30 keV) precipitation (FIREBIRD II and AC6 CubeSats, POES) to determine the size of the microburst‐producing chorus source region beginning on 5 December 2017. We estimate that the long‐lasting (∼30 hr) microburst‐producing chorus region extends from 4 to 8 ΔMLT and 2–5 ΔL. We conclude that microbursts likely represent a major loss source of outer radiation belt electrons for this event.